Essential Windows Workflow Foundation - Shukla, Dharma (Microsoft .NET development series., 2006)
"Something big is about to happen ..."--The Foreword by Don Box, Architect, Microsoft Corporation "If I were writing a Workflow book, this is what I would have written. The material is very well presented with code examples and explanations. Also, I love how the authors discuss the underlying architecture, enabling me to get a really deep understanding of the technology to efficiently design and build my own projects." -Jeffrey Richter (http://Wintellect.com) "Explicit support for workflows in a lightweight framework is a major contribution. Many tough problems traditionally faced by application authors, such as state management in the presence of long-running activities (think weeks or months!), can be addressed systematically by adopting a workflow approach. Dharma Shukla and Bob Schmidt present the workflow technology under and made accessible by the new workflow foundation in the .NET 3.0 framework, and they do so in an approachable and yet authoritative way that is truly enjoyable." -Clemens Szyperski, software architect, Microsoft Corporation "The Windows Workflow technology combines declarative programming and state machines in a very rich and powerful way, one that is bound to have a profound influence on the way we program in the coming years. In the style of the classic Essential COM by Don Box, Dharma and Bob have done a great job making this technology accessible to any developer already versed in C#, VB, and the .NET Framework, and who wants to achieve declarative enlightenment. Don't miss out." -Joe Duffy, program manager, Common Language Runtime (CLR) team, Microsoft Corporation "I think WF should and will be used as the main application model for web service applications. Developers working on web services will want to learn about this technology from this book; it comes straight from the source and explains the technology well and in depth." -Krzysztof Cwalina, program manager, Microsoft Corporation "This book provides an enlightening exploration of Windows Workflow Foundation for both the novice and the veteran alike." -Nate Talbert, software design engineer, Microsoft Corporation Windows Workflow Foundation (WF) is a groundbreaking approach to writing and executing programs. WF programs are assembled out of resumable program statements called activities, which provide encapsulation of both domainspecific logic and control flow patterns reflective of real-world processes. In Essential Windows Workflow Foundation, two ...